Advances in affective and pleasurable design : proceedings of the AHFE 2017 International Conference on Affective and Pleasurable Design, July 17--21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA /: proceedings of the AHFE 2017 International Conference on Affective and Pleasurable Design, July 17--21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA. ([2018]) - Unknown
No abstract available